Resistance of escherichia coli from rectal swab culture in hemato-oncology wards, dr. Soetomo hospital, surabaya - Rusanti, Rahmi; Rejeki, IGAA Putri Sri (Folia Medica Indonesiana, 2016)
Malignant hematology patients in the hospital are particularly susceptible to infection associated with endogenous microorganism originating from their own body. The most common etiology of infection is bacteria from gastrointestinal tract. Escherichia coli is a gram-negative facultative anaerobic bacteria, and part of the intestinal normal flora. However, E. coli is the most common cause of nosocomial infection. Resistance of E. coli to antibiotics has been widely reported. The aim of this study was to identify the development of antibiotic resistant properties of Escherichia coli from rectal swab of malignant hematology pediatric patients. A descriptive study of collected secondary data on sensitivity test results was done in the hematology-oncology pediatric ward, Dr. Soetomo Hospital from October 2012 to March 2013. There were 20 results of antibiotic susceptibility testing on positive Escherichia coli cultures from rectal swabs. The highest resistance levels were found towards cotrimoxazol, ampicillin sulbactam and cefotaxime. Escherichia coli with extended-spectrum b-lactamase (ESBL) was also found. Escherichia coli from rectal swabs of malignant hematology pediatric patients were shown to be resistant to cotrimoxazol, ampicillin sulbactam and ampicillin.